2015
DOI: 10.1371/journal.pone.0128215
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Nanotrap Particles in the Enhanced Detection of Rift Valley Fever Virus Nucleoprotein

Abstract: BackgroundRift Valley fever virus (RVFV) is a highly pathogenic arthropod-borne virus that has a detrimental effect on both livestock and human populations. While there are several diagnostic methodologies available for RVFV detection, many are not sensitive enough to diagnose early infections. Furthermore, detection may be hindered by high abundant proteins such as albumin. Previous findings have shown that Nanotrap particles can be used to significantly enhance detection of various small analytes of low abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Furthermore, the particles are capable of concentrating analytes of interest from large volumes of complex biological fluids (such as nasal aspirates) into a significantly smaller volume (as low as 25 mL). 9,10 At the heart of Nanotrap technology is a base particle consisting of a network of crosslinked environmentally-responsive polymer chains that have been functionalized with affinity baits to facilitate analyte capture and retention. 11 The versatility of the Nanotrap particles stems from the variety of affinity baits that can be immobilized onto the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the particles are capable of concentrating analytes of interest from large volumes of complex biological fluids (such as nasal aspirates) into a significantly smaller volume (as low as 25 mL). 9,10 At the heart of Nanotrap technology is a base particle consisting of a network of crosslinked environmentally-responsive polymer chains that have been functionalized with affinity baits to facilitate analyte capture and retention. 11 The versatility of the Nanotrap particles stems from the variety of affinity baits that can be immobilized onto the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] This novel sample preparation methodology has been utilized for the concentration and enhanced detection of infectious disease proteins, including a low-abundant bacterial antigen Outer surface protein A (OspA) used to diagnose Lyme disease 10 and the nucleoprotein of Rift Valley fever virus (RVFV). 9 While the Nanotrap particles were originally designed to specifically harvest proteins and other small molecules, recent findings by Shafagati et al have shown that the Nanotrap particles can also be used in the capture and detection of virions. 15 The ability of the Nanotrap particles to capture virions allows samples to be analyzed through numerous downstream analytical techniques (both protein and nucleic acid based) including standard sandwich ELISAs, lateral flow immunoassays, mass spectroscopy (MS) techniques, or q-RT-PCR assays.…”
Section: Introductionmentioning
confidence: 99%
“…Data are plotted as the geometric mean ± SEM from results of two independent experiments (n = 2). red 120 affinity bait allows NT particles to capture a wide range of RNA viruses (19,29). Using the newly developed magnetic NT particles could simplify workflows allowing the isolation of NT particles in 3-5 s instead of long centrifugation steps.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in our previous studies that NT particles capture and enrich various viruses, such as influenza virus and RVFV (19,21,29), but it has never been shown if NT particles can directly bind to viruses. Using transmission electronic microscopy (TEM) we visualized the direct interaction between NT particles and virions.…”
Section: Veev Binds To the Outside Of Nt Particlesmentioning
confidence: 90%
See 1 more Smart Citation